Cosmological model in modified Gauss-Bonnet gravity - Indira Nurat; Shynaray Myrzakul; Farida Belisarova
In this work, the Gauss-Bonnet model of modified gravity is investigated, where some arbitrary function  is added to the Einstein-Hilbert action. This theory explains the accelerated expansion of the Universe. In this work. The article proposes  modified gravity, which considers two gravities and , where  is a function from the Ricci scalar,  is a function from the Gauss-Bonnet invariant. The model is considered in a flat, isotropic and homogeneous Universe. As a result of some mathematical formalism, the dependence of the function  on the scalar of curvature  and on  time is found. Geometric and dynamic parameters of the cosmological model  were analyzed. Equations of motion and cosmological parameters, such as the Hubble parameter and scale factor, were obtained for the investigated model. Analyzing the obtained solutions of the scale factor, it was shown that the model describes the exponential acceleration of the Universe. Thus, it was found that the cosmological model under study has a similar interpretation to the de Sitter cosmological model.